Analysis of the Structure and Seasonal Variability of Food Waste in Urbanized Areas: Possible Actions for Achieve Sustainable Development - Veselá, Lucie; Vršanská, Martina; Baláková, Irena; Voběrková, Stanislava; Kubíčková, Lea; Vaverková, Magdalena Daria (John Wiley & Sons, Inc., 2025)
Food waste is a major global challenge with profound environmental implications. As urban populations continue to grow, effective waste management strategies will become increasingly important. This study aims to quantify food waste generated within mixed municipal waste from residential buildings and to analyze its seasonal variations. It examines consumer behavior, including motivations and barriers to food waste sorting. To achieve this, an analysis of mixed municipal waste and a questionnaire survey using computer-assisted web interviewing were conducted to gather insights from residents. The analysis revealed that food waste accounts for approximately 19.11% of mixed municipal waste, with notable seasonal variations, particularly during the summer months, when increased volumes are observed. Fruits and vegetables account for the largest share of avoidable food waste, with a peak in waste during the summer months. The results show seasonal fluctuations in food waste, highlighting the need for targeted waste management strategies. Consumer behavior analysis highlights key factors that influence the effectiveness of food waste collection, including the availability of infrastructure and motivational tools. To achieve a circular economy in cities, it is essential to implement efficient food waste sorting systems and improve consumer education. Optimizing these systems can significantly contribute to sustainable waste management. Raising consumer awareness and introducing appropriate motivational tools are key steps. This study supports efforts to achieve the sustainable development goal by proposing strategies to reduce food waste and improve urban waste management systems.
Keywords: circular economy; consumer habits; food waste; seasonality; sustainable development targets; urban sustainability; waste management